400PFemale lung cancer: Emerging issue in Bangladesh. (24th November 2019) - Islam, M R; Rahman, M; Khan, A A M; Alam, M J; Siddiqua, S M
Abstract: Background: Breast cancer is the leading killer of female cancer patient. Lung cancer became the second affecting cancer (12%) but the main killer (25%) in female cancer patient. (Cancer fact and Figures 2017" report published by American Cancer Society) and odd of getting lung cancer are 1 in 17. In Bangladesh, the status and features of female lung cancer is not clear. In western country, female are more prone to lung cancer due to some risk factor like smoking, alcohol, exposure of radon etc than Bangladesh. We tried to find out the socio-demographic status and clinical features of lung cancer of female in Bangladesh. Methods: This was a descriptive comparative observational study on 2396 female cancer patients reached at Outpatient of Medical oncology department of National Institute of cancer Research and Hospital, Mohakhali, Bangladesh from January 2018 to December 2018. Patients were selected purposive sampling method. Results: Total number of 2396 female patients were included in this study. The average age of female lung cancer patient was 56.12 years and average weight was 45.32kg. We had found 336 lung cancer patients (14%) among the 2396 female cancer patient. 58% were adenocarcinoma, 26% were Squamous Cell, 7% small cell variety with undifferentiated and others like Sarcoma, mesothelioma etc were 9%. Most of the patients were illiterate (59%) and 79% patient were poor or below average economically. 42% female patient didn't have any habitual problem. 46.82%% patients had the battle nut/ Jarda, 7.65% were smoker, about 10% had more than one habitual issue. At the time of presentation none of the had ECOG 0, patients had performance status O, most of the patient's performance status (ECOG) were 1 (58%) ECOG2 were 27%. 39% patient had comorbidity, among them most frequent comorbidity was Hypertension which was 39% and second was DM (33%) and 20% patient having more than one comorbidity. Conclusions: The percentage of female lung cancer in Bangladesh is pretty high among female cancer patient. female are most vulnerable group in rural area as well as they need special attention. Moreover, female lung cancer with other comorbidities makes the treatment more complicated for the cancer physician as well as brings the worst outcome. So, female lung cancer management should be personalized and comprehensive. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.